Safeguarding the Cultural and Natural Heritage of the Jukun People Through Music Composition and Performance - Ekpo, Omotolani Ebenezer; Loko, Olasunbo Omolara (Cultural Arts Research and Development, 2024)
The current wave of global changes and challenges in all areas of human existence and co-existence has concurrently necessitated the need, for deliberate preservation of world cultural and natural heritage. The Jukun people among other African tribes are vulnerable to various social, political, economic and natural threats capable of endangering the continuity of their cultural and natural heritage. The author’s ongoing ethnomusicological study of the composition and performance of music among the Wukari Jukun people of the southern Taraba state, Nigeria has revealed the roles of music in preserving these heritages. Employing the qualitative study approach, the study explored both oral and written works of literature on the posterity of the indigenous values, philosophy and natural endowments of the Jukun people over the decades.